2008
DOI: 10.1007/s11627-008-9123-4
|View full text |Cite
|
Sign up to set email alerts
|

Plantlet regeneration from leaf derived callus of Vanilla planifolia Andr.

Abstract: Vanilla planifolia is a tropical orchid mainly known for the aromatic flavor of its cured pods. Callus cultures were initiated from leaf and nodal explants of V. planifolia. Leaf explants showed better callus initiation than the nodal explants with callus biomass production maximal when cultured on Murashige and Skoog (MS) basal medium containing 4.52 mM 2,4-dichlorophenoxy acetic acid and 2.22 mM benzyladenine (BAP). Callus transferred to MS basal medium supplemented with 13.32 μM BAP, and 13.43 μM naphthalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 26 publications
2
23
2
4
Order By: Relevance
“…Among them are Aerides (Devi, Devi, & Singh, 2013), Aranda (Gantait, Bustam, & Sinniah, 2012), Phalaenopsis (Kuo, Chen, & Chang, 2005;Khoddamzadeh et al, 2011), Vanda and Dendrobium (Martin & Madassery, 2006;Tee, Wong, Lam, & Maziah, 2010), and Oncidium (Mayer, Stancato, & Appezzato-Da-Glória, 2010). In leaf cultures, for example in Renanthera (Wu et al, 2012) and Vanilla (Janarthanam & Seshadri, 2008), wound surface of leaf explants had been reported to produce callus. Wu et al, (2012) reported that 99.67 % plantlet formation was obtained from callus originated from leaf segments of Renanthera orchid.…”
Section: Introductionmentioning
confidence: 99%
“…Among them are Aerides (Devi, Devi, & Singh, 2013), Aranda (Gantait, Bustam, & Sinniah, 2012), Phalaenopsis (Kuo, Chen, & Chang, 2005;Khoddamzadeh et al, 2011), Vanda and Dendrobium (Martin & Madassery, 2006;Tee, Wong, Lam, & Maziah, 2010), and Oncidium (Mayer, Stancato, & Appezzato-Da-Glória, 2010). In leaf cultures, for example in Renanthera (Wu et al, 2012) and Vanilla (Janarthanam & Seshadri, 2008), wound surface of leaf explants had been reported to produce callus. Wu et al, (2012) reported that 99.67 % plantlet formation was obtained from callus originated from leaf segments of Renanthera orchid.…”
Section: Introductionmentioning
confidence: 99%
“…Orchids are propagated in vitro by using various explants such as shoot meristem, leaves, roots, protocorms etc. obtained from axenic cultures but the regenerative potential of pseudobulbs as explants has been less explored as compared to the other explants (Morel 1960, 1970, Stewart and Button 1976, Vajrabhaya 1978, Shimasaki and Uemoto 1987, Arditti and Ernst 1993, George and Ravishankar 1997, Vij and Kaur 1998, Kanjilal et al 1999, Pyati et al 2002, Decruse et al 2003, Basker and Narmatha 2006, Martin 2007, Janarthanam and Seshadri 2008, Medina et al 2009, Sungkum and Deb 2009, Sunitibala and Kishor 2009, Hong et al 2010, Mata-Rosas et al 2010, Kaur and Bhutani 2010, Rajkarnikar 2011, Pant and Thapa 2012. Therefore, an attempt was made to establish an efficient regeneration system by using pseudobulbs as explants for C. flaccida in particular checking the (i) influence of maturity level of pseudobulbs on regeneration potential, (ii) suitable culture medium, and the effect of growth regulators individually and in combination on regeneration of the explants and their successive development into plantlets (iii) induction potential of the apical and basal segments.There is no report on the development of in vitro methodology for mass propagation of C. flaccida using different explants.…”
Section: Introductionmentioning
confidence: 99%
“…Vanilla planifolia es cultivada comercialmente por sus frutos (cápsulas) de los cuales se extrae la sustancia aromatizante y saborizante llamada vainillina (George y Ravishankar, 1997;Geetha y Shetty, 2000;Giridhar y Ravishankar, 2004;Pak et al, 2004;Kalimuthu et al, 2006;Havkin-Frenkel y Belanger, 2007;Janarthanam y Seshadri, 2008;Chandran y Puthur, 2009;González-Arnao et al, 2009;Tan et al, 2010;Hailemichael et al, 2012). De los más de 250 compuestos diferentes aislados de los frutos de V. planifolia, la vainillina es el componente principal de las cápsulas fermentadas y es el sabor más ampliamente distribuido en el mundo (Pak et al, 2004;HavkinFrenkel y Belanger, 2007).…”
Section: Importancia De Vanilla Sppunclassified